Surface Hardness of Resin Cement Polymerized under Different Ceramic Materials - Pimmada Kesrak; Chalermpol Leevailoj (Hindawi Limited, 2012)
Objectives. To evaluate the surface hardness of two light-cured resin cements polymerized under different ceramic discs. Methods. 40 experimental groups of 2 light-cured resin cement specimens (Variolink Veneer and NX3) were prepared and polymerized under 5 different ceramic discs (IPS e.max Press HT, LT, MO, HO, and Cercon) of 4 thicknesses (0.5, 1.0, 1.5, and 2.0 mm), Those directly activated of both resin cements were used as control. After light activation and 37∘C storage in an incubator, Knoop hardness measurements were obtained at the bottom. The data were analyzed with three-way ANOVA, t-test, and one-way ANOVA. Results. The KHN of NX3 was of significantly higher than that of Variolink Veneer (𝑃<0.05). The KHN of resin cement polymerized under different ceramic types and thicknesses was significant difference (𝑃<0.05). Conclusion. Resin cements polymerized under different ceramic materials and thicknesses showed statistically significant differences in KHN.